2020
DOI: 10.21203/rs.3.rs-16282/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A health care record review of early mobility activities after fragility hip fracture: Utilizing the French systematic method to inform future interventions

Abstract: Background A fragility hip fracture is a serious injury in older adults. Following a fragility fracture, a large percentage of patients are unable to regain their pre-fracture level of mobility. There are several international guidelines recommending early mobility after surgery. We do not know the utilization of these early mobility recommendations by health care providers within our institution. An evidence to practice gap occurs when there is a failure to implement best practices. Utilization of a systemati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Research has demonstrated that early mobilization can reduce the duration of hospitalization and assist in restoring a patient's functional abilities, enabling them to return to their living situation prior to the fracture [4] . Recent studies indicate that the elderly population, who were able to walk before their fracture, spend more than 80% of their time in bed while hospitalized [7][8][9][10] . In 2011, a group of healthcare professionals at a major urban hospital in Toronto, Ontario, introduced the Bone & Joint National Model for Hip Fracture Care & Toolkit (2011) on a single unit dedicated to post-operative care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that early mobilization can reduce the duration of hospitalization and assist in restoring a patient's functional abilities, enabling them to return to their living situation prior to the fracture [4] . Recent studies indicate that the elderly population, who were able to walk before their fracture, spend more than 80% of their time in bed while hospitalized [7][8][9][10] . In 2011, a group of healthcare professionals at a major urban hospital in Toronto, Ontario, introduced the Bone & Joint National Model for Hip Fracture Care & Toolkit (2011) on a single unit dedicated to post-operative care.…”
Section: Introductionmentioning
confidence: 99%
“…The Hip Fracture Care & Toolkit was created with the aim of establishing and spreading the most effective methods for treating hip fractures throughout all provinces in Canada. 6 An analysis of the hip fracture population among older adults in this unit [10] revealed that early mobility activities are commenced within the first five days following surgery, with varying levels of implementation. A significant number of patients chose not to engage in early mobility activities, particularly among those with a low pre-fracture functional mobility level and those with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%